2009
DOI: 10.1111/j.1600-0404.2008.01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Post-polio syndrome: epidemiologic and prognostic aspects in Brazil

Abstract: Health professionals should carefully evaluate polio survivors for PPS and be aware of the implications of muscle overuse in the neurological recovery period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 23 publications
0
18
0
12
Order By: Relevance
“…22 No estudo de Conde, as queixas mais frequentes foram fadiga (87,1%), dor muscular (82,4%) e dor articular (72%). 23 Descobrimos que a prevalência de fadiga, dor articular e dor muscular foi significativamente maior no grupo SPP do que no grupo não SPP. A prevalência de distúrbios do sono foi semelhante em ambos os grupos.…”
Section: Resultsunclassified
“…22 No estudo de Conde, as queixas mais frequentes foram fadiga (87,1%), dor muscular (82,4%) e dor articular (72%). 23 Descobrimos que a prevalência de fadiga, dor articular e dor muscular foi significativamente maior no grupo SPP do que no grupo não SPP. A prevalência de distúrbios do sono foi semelhante em ambos os grupos.…”
Section: Resultsunclassified
“…The relationships between secondary conditions and age or duration of disease reported in the studies are inconsistent. For example one study 12 found no significant correlation between fatigue and age, but another study 13 found that fatigue was less common in individuals diagnosed between 43 and 57 years of age, relative to individuals diagnosed at an earlier age. More consistent findings were found for other conditions.…”
Section: Resultsmentioning
confidence: 99%
“…O grande problema dá-se quando tal população de neurônios remanescentes é sobrecarregada por muitos anos. Inicia-se um novo processo degenerativo com surgimento de um novo quadro sintomatológico 20 .…”
Section: Discussionunclassified
“…Conde et al 20 , fundamentadas a partir de pesquisas aos principais perió-dicos de expressão científica, os pacientes com SPP necessitam de intensa supervisão. Com relação à dor, os pesquisadores alertaram que o treinamento muscular inadequado pode exacerbá-la e contribuir para episódios agudos (Nível B).…”
Section: Discussionunclassified